2021
DOI: 10.1371/journal.pone.0251879
|View full text |Cite
|
Sign up to set email alerts
|

On the origins of American Criollo pigs: A common genetic background with a lasting Iberian signature

Abstract: American Criollo pigs are thought to descend mainly from those imported from the Iberian Peninsula starting in the late 15th century. Criollo pigs subsequently expanded throughout the Americas, adapting to very diverse environments, and possibly receiving influences from other origins. With the intensification of agriculture in the mid-20th century, cosmopolitan breeds largely replaced Criollo pigs, and the few remaining are mostly maintained by rural communities in marginal areas where they still play an impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Over the ensuing five centuries, increasing numbers of cattle were exported to North and South America particularly as the process of European coloniation intensified during the eighteenth and nineteenth centuries [6]. Evidence for a similar Iberian origin narrative has been described for sheep [7], pigs [8] and horses. For example, recent work has shown that historical and extant North American horse populations exhibit pronounced genetic affinities with Iberian horse populations [9].…”
Section: Introductionmentioning
confidence: 98%
“…Over the ensuing five centuries, increasing numbers of cattle were exported to North and South America particularly as the process of European coloniation intensified during the eighteenth and nineteenth centuries [6]. Evidence for a similar Iberian origin narrative has been described for sheep [7], pigs [8] and horses. For example, recent work has shown that historical and extant North American horse populations exhibit pronounced genetic affinities with Iberian horse populations [9].…”
Section: Introductionmentioning
confidence: 98%
“…Over the ensuing five centuries, increasing numbers of cattle were exported to North and South America particularly as the process of European colonization intensified during the 18 th and 19 th centuries [6]. Evidence for a similar Iberian origin narrative has been described for sheep [7], pigs [8], and horses. For example, recent work has shown that historical and extant North American horse populations exhibit pronounced genetic affinities with Iberian horse populations [9].…”
Section: Introductionmentioning
confidence: 99%